2020
DOI: 10.1016/j.joep.2019.102213
|View full text |Cite
|
Sign up to set email alerts
|

Overconfident health workers provide lower quality healthcare

Abstract: Overconfident health workers provide lower quality healthcareWhile a growing body of evidence suggests that healthcare workers in low and middle-income countries often provide poor quality of care, the reasons behind such low performance remain unclear. The literature on medical decision-making suggests that cognitive biases, or failures related to the way healthcare providers think, explain many diagnostic errors. This study investigates whether one cognitive bias, overconfidence, defined as the tendency to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Together with a growing body of evidence, this paper shows that higher workloads do not necessarily lead to worse quality of care. A future agenda of research has to go beyond these traditional explanations and explore other drivers of poor provider performance – for instance, cognitive biases might play an important role in limiting the performance of primary care providers in LMICs ( Kovacs et al., 2020 ). In the absence of such evidence, governments run the risk of wasting limited resources on interventions that do not lead to improvements in health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Together with a growing body of evidence, this paper shows that higher workloads do not necessarily lead to worse quality of care. A future agenda of research has to go beyond these traditional explanations and explore other drivers of poor provider performance – for instance, cognitive biases might play an important role in limiting the performance of primary care providers in LMICs ( Kovacs et al., 2020 ). In the absence of such evidence, governments run the risk of wasting limited resources on interventions that do not lead to improvements in health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Overconfidence, defined as "greater confidence than reality justifies" [1, p. 1], has been termed "one of the most consistent, powerful and widespread" among psychological biases [2, p. 317] and the "rarely addressed mother of all biases" in medicine [3, p. 127]. To date, overconfidence in medicine has been primarily studied as a cause of diagnostic errors [4,5], and one study found poor case management by overconfident health care workers [6]. As regards infection prevention and control (IPC), particularly hand hygiene, overconfidence has been argued to represent a barrier to professionals' compliance with interventions to prevent health care-acquired infections (HAIs) in some but, given pertinent clinical experiences, surprisingly few studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Overconfidence plays a key role in shaping behavior, at least in some domains (e.g., refs. [6][7][8][9][10]. However, we know very little about its potential role in the spread of false news.…”
mentioning
confidence: 99%